Improving Students Reading Comprehension Achievement in Narrative Text Through Experience Text Relationship Method At VIII Grade MTs Al- Jam’iyatul Washliyah Tembung. - farda repelitawaty (VISION, 2018)
This research was aimed to know the students’ reading comprehension achievement in narrative text through experience text relationship method. The research was conducted by using classroom action research. The subject of this study was 43 students at eight grade of MTs Al- Washliyah Tembung Medan in academic year 2016/2017. The research was conducted in two cycles, cycle I consisted of three meetings and cycle II consisted of three meetings. The data of this research were qualitative data was taken from interview, observation, diary notes, documentation. And the quantitative data was taken from the test. The result of the data analyzing showed from mean of pre-test was 53.02 and the mean of the students score for the post test I in the first cycle was 77.44 and post test II in the second cycle was 92.09. The percentage of the students’ achievement in learning narrative text in pre-test was 16.27% which is lower than the post test I was 72.09%, and lower than post test II was 100%. And based interviewed, observation sheet, diary notes and documentation showed that the students’ response at reading comprehension in narrative text through experience text relationship method was very good. It was found that teaching reading narrative text by experience text relationship method could improve the students’ achievement.Keywords: Reading Comprehension, Narrative Text, Experience Text Relationship Method.